THE EFFECT OF KNOWLEDGE SHARING ON EMPLOYEE PERFORMANCE AT PT TAMA COKELAT INDONESIA - nurrachman, qeisha; hermanto, bambang; chan, arianis (Archives of Business Research, 2019)
Knowledge is currently viewed as an important strategic resource in companies in order to gain competitive advantage. This study aims to analyze the effect of Knowledge Sharing on the performance of PT Tama Cokelat Indonesia employees. Knowledge sharing variables are measured by knowledge donating and collecting, while employee performance variables are measured by the quality of work, quantity of work, knowledge of work, cooperation, reliability, initiative and personal quality. The approach used is a quantitative approach with a survey method for employees of PT Tama Cokelat Indonesia totaling 69 respondents. This research is the result of a questionnaire distributed to all objects that became observations / research. The results of this study indicate that knowledge sharing has a positive and significant effect on employee performance. These variables were analyzed using descriptive statistics for supporting data and Component Based SEM or Partial Least Square (PLS) regression analysis in the research data.